2023
DOI: 10.1186/s12917-023-03588-2
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted metabolomics reveals alternations in metabolism of bovine mammary epithelial cells upon IFN-γ treatment

Abstract: Background IFN-γ is a pleiotropic cytokine that has been shown to affect multiple cellular functions of bovine mammary epithelial cells (BMECs) including impaired milk fat synthesis and induction of malignant transformation via depletion of arginine, one of host conditionally essential amino acids. But the molecular mechanisms of these IFN-γ induced phenotypes are still unknown. Methods BMECs were treated with IFN-γ for 6 h, 12 h, and 24 h. The met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…This finding suggests that persistent or repeated bacterial infections may impact the properties of mammary epithelial cells, leading to alterations in amino acid metabolism in milk, which are caused by changes in subsequent lactation. A recent study demonstrated that treatment with IFN-γ, an immune-regulatory cytokine, in bovine mammary gland epithelial cells, resulted in significant changes in metabolite profiles, including arginine and proline metabolism [ 39 ]. Further investigations are warranted to elucidate the underlying mechanisms of repeated infections and/or caused changes in mammary gland tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that persistent or repeated bacterial infections may impact the properties of mammary epithelial cells, leading to alterations in amino acid metabolism in milk, which are caused by changes in subsequent lactation. A recent study demonstrated that treatment with IFN-γ, an immune-regulatory cytokine, in bovine mammary gland epithelial cells, resulted in significant changes in metabolite profiles, including arginine and proline metabolism [ 39 ]. Further investigations are warranted to elucidate the underlying mechanisms of repeated infections and/or caused changes in mammary gland tissue.…”
Section: Discussionmentioning
confidence: 99%